Pengaruh Mikroba Dalam Proses Fermentasi Pembuatan Tempe - Wulan Permata Sari; Tata Lathifatul ‘Ainiyah; Verel Marcellina; Theresia Vida Sabrina; Liss Dyah Dewi A (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Tempeh is the result of fermented soybeans. In the fermentation process, the white tissue in tempeh is made from mycelium which is a species of the genus Rhizopus. Tempeh is generally boiled and fermented with the mold Rhizopus sp. Tempeh has the enzyme phytase which plays a role in reducing phytic acid in soybeans due to the role of mold. This research was carried out using the literature study method in the form of textbooks, papers from scientific journals and proceedings. Collect literature and create a summary which will then be analyzed and synthesized in depth. Good quality tempeh is characterized by an even white color on the entire surface, a united structure, if cut it remains intact and does not fall out easily, and has a distinctive aroma without a strong odor. In order to create appropriate product quality, there must be quality standardization. With the aim of maintaining product results that meet standards so that consumers will always trust the product in question. Tempe is a fermented soybean product made from Rhizopus mycelium, producing protease enzymes and phytase enzymes. Fermentation converts carbohydrates into alcohol or acids, forming lactic and acetic acids. This process, which takes one to two days at a temperature of 30ºC – 32ºC, increases the nutritional value of soybeans by breaking down carbohydrates and proteins.